2024
DOI: 10.3390/polym16020278
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Novel SrTiO3/MnO2 Hybrid Nanoparticles on Poly(methyl methacrylate) Thermal and Mechanical Behavior

Houda Taher Elhmali,
Ivana Stajcic,
Aleksandar Stajcic
et al.

Abstract: While dental poly methyl methacrylate(PMMA) possesses distinctive qualities such as ease of fabrication, cost-effectiveness, and favorable physical and mechanical properties, these attributes alone are inadequate to impart the necessary impact strength and hardness. Consequently, pure PMMA is less suitable for dental applications. This research focused on the incorporation of Strontium titanate (SrTiO3-STO) and hybrid filler STO/Manganese oxide (MnO2) to improve impact resistance and hardness. The potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…As can be seen, the shape and size of the agglomerates in PMMA-SrTiO3, PMMA-MnO2 and SrTiO3/MnO2 vary, with different toughening mechanisms observed at the fracture surface. In our previous research, it was shown that the synergy between SrTiO3 and MnO2 resulted in an improved mechanical performance compared to both the pure PMMA and PMMA-SrTiO3 composite [18]. This was a consequence of the reduced agglomeration and better distribution of ceramic particles within the polymer matrix.…”
Section: Fesem Analysis Of Compositesmentioning
confidence: 96%
See 1 more Smart Citation
“…As can be seen, the shape and size of the agglomerates in PMMA-SrTiO3, PMMA-MnO2 and SrTiO3/MnO2 vary, with different toughening mechanisms observed at the fracture surface. In our previous research, it was shown that the synergy between SrTiO3 and MnO2 resulted in an improved mechanical performance compared to both the pure PMMA and PMMA-SrTiO3 composite [18]. This was a consequence of the reduced agglomeration and better distribution of ceramic particles within the polymer matrix.…”
Section: Fesem Analysis Of Compositesmentioning
confidence: 96%
“…SrTiO 3 , MnO 2 and SrTiO 3 /MnO 2 were incorporated into a dental PMMA matrix. SrTiO 3 /MnO 2 nanoparticles were prepared by the previously published procedure, with a particle concentration of 1 wt% in all composites [18]. The scheme presented in Figure 1 shows the experimental procedure for composite preparation.…”
Section: Processing Of Composite Materialsmentioning
confidence: 99%